A COMPASS for Navigating Relationships in Co-Production Processes Involving Vulnerable Populations. Issue 9 (4th July 2021) - Mulvale, Gillian; Miatello, Ashleigh; Green, Jenn; Tran, Maxwell; Roussakis, Christina; Mulvale, Alison
ABSTRACT: When it comes to engaging vulnerable populations in co-production, power imbalances across stakeholder groups can create methodological challenges. A thoughtful, planned, and responsive approach is needed to prepare vulnerable participants to fully engage in co-production processes. Data from key informant interviews (n = 16) and author reflections on three Experience-based co-design (EBCD) studies involving youth (16–25 years) with mental health issues in Ontario Canada, were analyzed. Four overarching themes and 12 subthemes were identified, and heuristic tools (a relational COMPASS and MAPS directions) were developed to assist researchers in navigating vulnerability, power and relational issues in co-production processes involving vulnerable populations.